China's economic growth and rebalancing - Ettore Dorrucci; Gabor Pula; Daniel Santabárbara (European Central Bank (ECB), 2013)
In this paper we provide an overview of the growth model in China and its prospects, taking a medium-run to long-run perspective. Our main conclusions are as follows. First, the still prevailing producer-biased model of managed capitalism in China tends to engender, as an inherent byproduct, serious imbalances which cannot be unwound without a fundamental overhaul of the model itself. Second, given the lack of a critical mass of economic reforms thus far, imbalances may (re-)escalate once global and domestic economic conditions normalise. Third, the fundamental factors underpinning growth in China are likely to remain supportive, at least over the medium run. Although this could help mitigate the economic costs of imbalances for some time to come, it could also reduce the incentives for policy-makers to enact much needed reforms. Fourth, delayed policy action and the persistence of the model of growth cum imbalances would increase the risk of China getting caught in the middle-income trap in the long run. Greater political will to redirect China's growth model towards a more sustainable path is therefore needed.
Keywords: C22; C51; C53; C59; 330; China; Economic Growth; imbalances; middle-income trap; rebalancing; Exportinduziertes Wachstum; Wirtschaftsreform; Nachhaltige Entwicklung; China